PENGARUH MODEL PEMBELAJARAN TECHNOLOGICAL PEDAGOGIC AND CONTENT KNOWLEDGE (TPACK) TERHADAP KOGNISI SISWA SEKOLAH DASAR - Ramdhan Witarsa; Parulian Siregar (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Kediri, 2023)
The technological pedagogic and content knowledge aims to develop the cognition of primary school students. This research aims to measure how much influence the technological pedagogic and content knowledge learning model has on primary school students' cognition. The method used in this research is quasi-experiment. This method has nine stages: literature review, identifying and limiting research problems, developing research hypotheses, creating research designs, conducting pretests, conducting experiments, conducting post-tests, processing and analyzing data, and drawing conclusions. The research sample totaled 20 students, consisting of 10 students in the experimental class and 10 in the control class. The data collection technique used was a student cognition test. The results showed that the technological pedagogic and content knowledge learning model significantly affected elementary school students' cognition in-class experiments.